Peran Koperasi Unit Desa Cahaya dalam Peningkatan Ekonomi Petani Kelapa Sawit di Desa Sinunukan Kecamatan Sinunukan Kabupaten Mandailing Natal Provinsi Sumatera Utara - Rozikin, Rozikin; Purwandari, Istiti; Listiyani, Listiyani (AGRIFITIA : Journal of Agribusiness Plantation, 2025)
Cooperatives are business entities owned and utilized by members. Cooperatives are business entities that aim to build and develop the economic capabilities of their members. This study aims to determine the types of services of the Cahaya Village Unit Cooperative in oil palm farmers' businesses and to determine the role of the Village Unit Cooperative in improving the economy of oil palm farmers in Sinunukan Village, Sinunukan District, Mandailing Natal Regency, North Sumatra Province. This research method was determined intentionally (purposively), namely the Cahaya Village Unit Cooperative (KUD) in Sinunukan Village. The method used in sampling was purposive sampling, by selecting active farmers. The data used in this study were primary and secondary data. The results of the study showed that the services of the Cahaya Village Unit Cooperative (KUD) in Sinunukan Village for oil palm farmers' businesses included the provision of production services, service services, savings and loan services, and marketing services. The Cahaya Village Unit Cooperative (KUD) in Sinunukan District plays a role in improving the economy of oil palm farmers